2014
DOI: 10.1007/s00345-014-1447-6
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable continence therapy (ProACT™) after male sling failure for patients with post-radical prostatectomy urinary incontinence: a prospective study with one-year follow-up

Abstract: The Pro-ACT™ device may provide additional benefits for improving continence in case of persistent incontinence following male sling insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…An additional indication for the ProACT therapy in elderly patients, who cannot undergo major surgery or avoid an active system due to a lack of manual dexterity . ProACT can also be implanted in failed sling patients and has shown favorable functional results . More research is needed to determine who may be the best candidates for ProACT as a first‐line therapy vs patients who will likely not benefit as greatly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional indication for the ProACT therapy in elderly patients, who cannot undergo major surgery or avoid an active system due to a lack of manual dexterity . ProACT can also be implanted in failed sling patients and has shown favorable functional results . More research is needed to determine who may be the best candidates for ProACT as a first‐line therapy vs patients who will likely not benefit as greatly.…”
Section: Discussionmentioning
confidence: 99%
“…19 ProACT can also be implanted in failed sling patients and has shown favorable functional results. 9,25 More research is needed to determine who may be the best candidates for ProACT as a first-line therapy vs patients who will likely not benefit as greatly. However, ProACT should be considered for all patients presenting with SUI that desire surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Only one publication focuses on PUB after failed slings. 18 In this prospective study that included 20 patients, Yiou et al concluded in favor of ACT as an alternative to sling removal and AUS implantation, with 66.7% patients healed. Our results corroborate their conclusion, with 26 patients improved (96.3%) and 18 healed (66.7%).…”
Section: Discussionmentioning
confidence: 90%
“…One study reported that while ProACT device appears to be safe and efficacious in the short term, postoperative readjustment allows for achievement of a short-term continence and in the long-term, the ProACT does not appear to be an ideal device for durable continence and patients’ satisfaction with less than 5% of patient being dry and 45% of patients remained satisfied with ProACT device at median follow-up of 57 months (69). Nonetheless it appears that ProACT device may provide some additional benefits for improving continence in case of persistent incontinence after male sling insertion (70). Common complications of ProACT device include balloon migration, pain, infection and recurrent incontinence.…”
Section: Methodsmentioning
confidence: 99%